Transport Economies in the Euro-Mediterranean Region (Study on Key Indicators of Arab Regional Transport Integration in the Euro-Mediterranean Area) - Noudjoud, Hamri; Nassira, Selmi (Journal of Ecohumanism, 2025)
In the global economy, economic opportunities and the economic success of any country or region are linked to the quality of transport infrastructure, which enables the safe and efficient movement of people and goods. Transport economies are therefore essential for the development and sustainability of international trade. This study confirms that regional integration of transport systems in the Euro-Mediterranean region relies on integrating interoperability and logistics concepts at the project design stage, benefiting all partners. The study concludes that geographic proximity will only be meaningful if the maritime routes of Southeast Mediterranean countries are integrated with the European interface, and sustainable transport integration in the Euro-Mediterranean region will not be achieved unless these countries are actively involved in an efficient regional transport network supported and financed by Europe.